Analysis of the feasibility of investing in the use of electric motors in online drivers - I Gede Marendra; I Made Aryata (Institute of Computer Science (IOCS), 2023)
The high number of motorbike users in Indonesia in 2020 of 115,023,039 units also contributed to high air pollution where motorbikes contributed 45% to the resulting vehicle pollution. Based on Jakarta's air quality index (AQI) data on January 18, 2023, an AQI value of 101 was obtained which is unhealthy for sensitive groups, of course a strategy is needed to increase the use of electric motorbikes to reduce air pollution produced by conventional motorbikes. Online drivers are a market segment that can be used as a priority for the transition to electric motorcycles, considering that the mobility of online drivers is quite high, which is around 230 km/day. Providing soft loans can be the best option to attract online drivers to switch to using electric motorbikes. Based on the results of calculations using the daily installment payment scheme for the investment of electric motors and battery motors, the total return that must be paid on the investment of electric motors and electric motor batteries is Rp. 30,168,885 and Rp. 8,021,370 where the annual interest that must be paid by online drivers is still less than the bank loan interest of 8.75%. In terms of financial feasibility, the NPV that online drivers will receive is Rp. 5,343,823, IRR of 18.88% and Payback Period for 6 years 1 months.